DIVERSITÉ FLORISTIQUE ET STRUCTURALE DES CACAOYÈRES DU « V BAOULÉ » : CAS DE LA SOUS-PRÉFECTURE DE KOKUMBO (CENTRE, CÔTE D’IVOIRE) - Bruno, Kpangui Kouassi; Aimé, Vroh Bi Tra; Bertin, Goné Bi Zoro; Yves, Adou Yao Constant (European Scientific Journal, ESJ, 2015)
In the Center of Côte d’Ivoire, cocoa introduction and the maintenance of its cultivation were possible thanks to the adoption of agroforestry practices from long time. Nowadays, for the rehabilitation of these old farms, peasants use new cocoa varieties which do not tolerate the shade. An analysis of these farming systems was carried out around Kokumbo, in forest-savannah transitional zone. The objective of this study was to assess floristic diversity of cacao-plantations according to their ages. Data were gathered using itinerant censuses and square plots (625 m2 ), in various age groups of plantations, forest patches being used as witnesses. At the end of the analysis, it appears that the hybrid varieties "Ghana" and "Mercedes" are mainly cultivated in young cocoa plantations (less than 30 years)."Français" variety remained on the other hand exclusive with the old farms. Species richness is made of 166 species in cacao farms and 275 species forests patches. In young cocoa-based agroforestry systems, the large forest trees are gradually replaced by exotic or indigenous fruit species, which does not affect the species richness, the diversity and density of the stems. In the old systems, the high density of large diameters individuals confers to them basal area similar to that of forest patches. This study shows that agroforestry practices still ongoing despite of the use of new cocoa varieties. However, the use of new cocoa hybrids could over time attend local plant species diversity erosion in cocoa farms.